Farmers’ Capacity in Climate Change Adaptation through Climate Field School in Banyurip Village, Pekalongan City - Azizah, Nur; Banowati, Eva; Hayati, Rahma (JESS (Journal of Educational Social Studies), 2019)
Failure to harvest that caused by weather/climate factors is a serious problem for farmers. There problems cause low productivity of farmers. Climate field school became a solution to increase the farmer’s capacity in managing agricultural area. The purpose of this study is to examine the capacity of farmers from climate change. Analyzing the adaptation of farmers to climate change. This research was conducted quantitatively with quantitative descriptive methods. The population of this study was all 25 farmer participants of CFS. The techniques of collecting data were through questionnaires and interviews. Data analysis techniques using questionnaire data analysis and descriptive analysis. The results in this study showed that the farmers’ capacity in the Banyurip Village had a very high capacity with an average percentage which is reaching 76.4%. Farmer adaptation strategies to climate change are increasing, which is marked by a change from conventional way to more effective and efficient treatments. Farmer adaptation behavior is characterized by increased attitudes in the management of irrigation systems, determination of tolerant rice varieties, analysis of soil content and study of cropping patterns.